Field of view determination and spatial calibration of night airglow all-sky images - Patil, P.T.; Patil, R.P.; Ghodpage, R.N.; Patil, S.B.; Nade, D.P. (My University, 2015)
The various phenomenon and structures observed in night airglow all-sky imager (ASI) images (such as, drift motions of gravity waves and plasma bubbles) these are accurately measured only after the spatial calibration of the images. While spatial calibration is a process of computing pixel to real-world unit transformations although accounting for many errors inherent to the imaging setup. Calibration of image is important when accurate measurements required in real-world units. In this paper spatial calibration includes the alignment to true north and measurement of field of view (FOV) of captured ASI images. For the spatial calibration the stars in the (ASI) image are used as a reference points which is then compared and calibrated with star catalogue image to find true north and FOV of ASI image. The spatial calibration and FOV measurement of an image is useful when the imaging setup is not stationary. This paper presents developed simple but accurate methodology for spatial calibration and FOV measurement of ASI image. The software is developed for the FOV measurement and spatial calibration by using Mat Lab 7.0.
Keywords: Night airglow; Star map; Field of view; True north; All-sky imager